Các yếu tố tác động đến ý định sử dụng sản phẩm cho vay ngang hàng: Tích hợp lý thuyết hành động hợp lý và mô hình chấp nhận công nghệ - Nguyễn Viết, Bằng; Nguyễn Thị Nhất, Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Peer-to-peer (P2P) lending is a relatively new yet swiftly proliferating trend within the realm of digital finance, coexisting with other technologies such as e-wallets, cryptocurrencies, and mobile banking. P2P Lending directly connects borrowers with lenders without going through financial intermediaries, replacing it with a platform using digital technology. This study integrated the Reasoned Action Theory and Technology Acceptance Model to clearly understand the factors and extent of the impact on intention to use in the context of P2P Lending products. This study follows a quantitative approach through interviews with 217 participants who had loan needs. Research results show that borrower intention is affected by trust, usefulness, and platform reputation. Our research has meaningful implications for marketers and banking/financial managers in that marketers should be more proactive in improving people’s intention to use peer-to-peer lending.